Ornamental feathers in Cretaceous Burmese amber: resolving the enigma of rachis-dominated feather structure - Lida Xing (Journal of Palaeogeography, 2018)
Abstract Over the last 20 years, compression fossils of feathers surrounding dinosaurs have greatly expanded our understanding of the origin and evolution of feathers. One of the most peculiar feather morphotypes discovered to date are rachis dominated feathers (RDFs), which have also been referred to as proximally ribbon-like pennaceous feathers (PRPFs). These elongate feathers are only found in the tail plumage, typically occurring in pairs with both streamer (not proximally ribbon-like) and racket-plume morphologies recognized. Here we describe a large sample set of isolated and paired RDFs from Upper Cretaceous Burmese amber (~ 99 Ma). Amber preserves the finest details of these fragile structures in three dimensions, demonstrating that RDFs form a distinct feather morphotype with a ventrally open rachis, and with significant variability in pigmentation, microstructure, and symmetry.